Impact of spreading bandwidth on RAKE reception in dense multipath channels. - Win, M.Z (IEEE Journal on selected areas in communications)
Spread spectrum (SS) multiple access techniques have been proposed for third generation broadband wireless access. We develop an analytical framework to quantify the effects of spreading bandwidth on SS systems operating in dense multipath environments in terms of the receiver performance, receiver complexity, and multipath channel parameters. In particular, we consider wide-sense stationary uncorrelated scattering (WSSUS) Gaussian channels with frequency-selective fading. The focus of the paper is to characterize the combined signal of the RAKE receiver fingers tracking the strongest multipath components. Closed form expressions for the mean and the variance of the total RAKE receiver output signal-to-noise ratio (SNR) are derived in terms of the number of RAKE fingers, spreading bandwidth, and multipath spread of the channel. The proposed problem is made analytically tractable by transforming the physical RAKE paths into the virtual path domain. A representative result indicates that for SS systems with 5 MHz signal bandwidth operating in a channel with constant power delay profile having 5 μs spread, the average SNR gain from increasing the number of RAKE fingers from one to three is 3.8 dB and from three to five is 1.5 dB. Furthermore, the reduction in the variation of SNR is 1.1 dB and 0.4 dB for the same increments in the number of fingers